Association of shivering threshold time with body composition and brown adipose tissue in young adults. (August 2022) - Sardjoe Mishre, Aashley S.D.; Martinez-Tellez, Borja; Acosta, Francisco M.; Sanchez-Delgado, Guillermo; Straat, Maaike E.; Webb, Andrew G.; Kan, Hermien E.; Rensen, Patrick C.N.; Ruiz, Jonatan R.
Abstract: Purpose: Brown adipose tissue (BAT) increases metabolic heat production in response to cold exposure. Body size and composition are involved in the human cold response, yet the influence of BAT herein have not fully been explored. Here, we aimed to study the association of the cold-induced shivering threshold time with body composition, BAT, the perception of shivering and skin temperature in young adults. Methods: 110 young healthy adults (81 females; age = 21.7 ± 2.1 years, BMI = 24.2 ± 4.3 kg/m 2 ) underwent 2 h of individualized cooling, followed by the quantification of BAT using a 18 F-fluorodeoxyglucose ([ 18 F]FDG) positron emission tomography-computed tomography (PET-CT) scan. Body mass index (BMI), lean mass, fat mass and body surface area (BSA) were also measured. Shivering threshold time was defined as the time until shivering occurred using an individualized cooling protocol. Results: The shivering threshold time was on average 116.1 min for males and 125.8 min for females, and was positively associated to BMI (β = 3.106; R 2  = 0.141; p = 0.001), lean mass (β = 2.295; R 2  = 0.128; p = 0.001) and fat mass (β = 1.492; R 2  = 0.121; p = 0.001) in females, but not in males (all p ≥ 0.409). The shivering threshold time was positively associated with BSA in males (p = 0.047) and females (p = 0.001), but it was not associated with BAT volume or [ 18 F]FDG uptake nor with the perception of shivering and skin temperature perception in both sexes. Conclusion: The shivering threshold time is positively associated with whole-body adiposity and lean mass in females, but not in males. The shivering threshold time was positively associated with BSA, but no association was observed with BAT nor with the perception of shivering or skin temperature. Future research should consider the influence of body composition when applying cooling protocols among individuals with different phenotypical features. Highlights: Shivering threshold time is positively associated with body composition only in females. Shivering threshold time is positively associated with body surface area in males and females. Shivering threshold time is not related to BAT volume or 18 F-FDG uptake. Shivering threshold time is not related to the perception of shivering or skin temperature.